New Formulations of Ni-Containing Ceramic Papers to Enhance the Catalytic Performance for the Oxidative Dehydrogenation of Ethane - Bortolozzi, Juan Pablo (2014)
Ceramic papers composed of silica–alumina fibers structured using colloidal suspensions as binders constitute interesting materials to be used as flexible supports of catalytic materials. The deposition of Ni as the active ingredient together with Zr or Ce promoters resulted in active and selective structured catalysts for the oxidative dehydrogenation of ethane; these structured catalysts also exhibited acceptable mechanical properties. The employed binder agents (nanoparticles of ceria, zirconia, or yttria-stabilized zirconia) homogeneously covered the fiber surface, contributing to the dual function of building a three-dimensional arrangement and favoring the anchoring of the catalytic formulations. The prepared papers showed nickel oxide as the active phase. The incorporation of cerium or zirconium as promoters enhanced the catalytic properties. The former element mainly produced an increase in ethane conversion, whereas the latter markedly improved ethylene selectivity. In both cases, an ethylene productivity was obtained in the promoted systems which was higher than that in the unpromoted samples. It is likely that the formation of the solid solutions Ni–Ce–O and Ni–Zr–O, as suggested by X-ray diffraction and laser Raman spectroscopy analyses, plays an important role in these effects. The best catalyst was the one containing nickel as the active phase, Ce as the promoter, and ZrY as the binder agent, for which ethylene productivity at 400 °C was ca. 513 g ethylene/(kgcat h). The binder agent addition was necessary to join the fibers, thus improving the mechanical properties of the papers, but they also affected the catalytic performance through the coverage of ceramic fibers and the resulting interaction with the catalytic compounds. The performed tensile index tests showed that the colloidal suspension of ceria produced papers with mechanical properties better than those of zirconia or zirconia–yttria because they exhibited greater resistance and flexibility.